A chemotherapy privileging process for advanced practice providers at an academic medical center. (January 2020) - A Carrasquillo, Michelle; A Vest, Tyler; S Bates, Jill; Faso, Aimee; Auten, Jessica; Buchanan, Ian; McCann, Meghan; Carey, Lisa; Amerine, Lindsey B
Purpose: Nurse practitioners, physician assistants, and pharmacists are advanced practice providers who are highly trained and qualified healthcare professionals that can help support traditional demands on oncologists' increased time in direct patient care. The purpose of this study was to detail and assess the creation of a privileging process for this group of medical professionals within an academic medical center. Obtaining the designation of limited oncology practice provider (LOPP) gives the right to modify chemotherapy orders and to order supportive care medications. Methods: An interdisciplinary team developed a comprehensive training process inclusive of required educational domains, knowledge goals, and educational activities to become an LOPP. In 2018, five years after the implementation of the privileging process, a survey was distributed to assess perceptions of the training process and integration of LOPPs within oncology practice. Results: Most oncologists noted that working with LOPPs is beneficial to oncology practice (94%) and that they make modifying chemotherapy orders more efficient (87%). Greater than 82% of LOPPs also reported that their privileges streamline the chemotherapy process and make them feel valuable. Conclusion: The creation of the LOPP designation is an effective way to integrate nurse practitioners, physician assistants, and pharmacists within oncology practice. The inclusion of a focused privileging process ensures the safety of cancer care provided and has created a streamlined process for chemotherapy modifications and supportive care.